Metabolic Syndrome and Benign Prostatic Hyperplasia: A Nepalese Perspective - Chhetri, Raj Kumar; Baral, Suman; Thapa, Neeraj (Journal of Lumbini Medical College, 2018)
Introduction: Metabolic syndrome is defined as the presence of at least 3 of the following parameters: (1) waist circumference ≥ 90 cm, (2) triglycerides > 150 mg/dl or treatment for hypertriglyceridemia, (3) HDL-cholesterol < 40 mg/dl or treatment for reduced HDL-cholesterol, (4) blood pressure ≥ 130/85 mmHg or current use of antihypertensive medications, (5) fasting blood glucose ≥ 110 mg/dl or previous diagnosis of type-2 diabetes mellitus. It is closely associated with many diseases and recent studies have also shown its association with benign prostatic hyperplasia and lower urinary tract symptoms. Our study aimed to investigate association between metabolic syndrome and its components with benign prostatic hyperplasia among patients managed surgically in a tertiary centre in Western Nepal. Methods: One hundred and four patients above 50 years with benign prostatic hyperplasia managed in the department of Surgery over one year were included in the study. Results: Twenty-seven patients had metabolic syndrome (25.96%). There was association between metabolic syndrome and mean prostate size and among components of metabolic syndrome, high serum triglyceride and low HDL Cholesterol were found to be associated. There was increase in mean prostate size with increase in number of metabolic syndrome components which was statistically significant. Conclusion: Metabolic syndrome along with its two components, serum triglyceride and HDL Cholesterol were associated with increase in mean prostate size. DOI: https://doi.org/10.22502/jlmc.v6i2.207